Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Gulf of Mexico)--American oyster - Stanley, Jon G.; Sellers, Mark A. (Washington, D.C. U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.64)
Keywords: Invertebrates; Fishes; History; American oyster--Gulf of Mexico